Analisa Teoritis Kebutuhan Daya Mesin Bubut Gear Head Turret - Iskandar, Wahyudi; , Supriyono, ST, MT, Ph.D (2016)
In the process of turning require power, in which the power obtained from electrical energy. The electrical energy is then converted into mechanical energy via an electric motor. How much power the electric motor is determined by several factors, among others: cutting speed, depth of cut, motion eating, cutting time and cutting tool material. In modern lathe used system is to make the gear head gear as the transmission power is driven by an electric motor. So that there is a relationship between the electric motor power on a lathe with head gear system to the cutting depth on a lathing process. The process of turning the workpiece AISI 1020 BHN 175, carbide tool with cutting tool angle of 300, cutting speeds of 300 fpm, motion eat 0.025 ipr, with variations in the depth of cut of 0.1 mm, 0,2mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm and 0.7 mm obtained will power the electric motors that vary according to the depth of cuts. The results of a theoretical analysis of the power requirements of gear head lathe turret with a variation of the cutting depth can be concluded that the theory obtained vary linearly extending line y = 2,6423x. So the deeper the cuts, the greater the power needed to cut on a lathe turret head gear.